Ethnopoetics and Narrative Analysis - Atkinson, Paul; Carver, Natasha (Narrative Works)

(untitled) (Centre for Interdisciplinary Research on Narrative, St. Thomas University, 2020)
We acknowledge and concur with Catherine Kohler Riessman’s insistence on the necessity of sustained and formal analysis of narratives. We thus distance ourselves from qualitative researchers who aim to celebrate personal narratives rather than undertaking that analytic work. In doing so, we also draw on the work of Dell Hymes, whose approach to ethnopoetics informs our own. The discussion is developed and illustrated with materials from Natasha Carver’s research with informants of Somali heritage that display the relevance of ethnopoetic transcription and analysis.